(untitled) (Annals of Medical Research, 2023)
Aim: The development of technology increases the rate of everyone having a smartphone. Therefore, the possible biological effects of these devices are of concern. In this study, we aimed to investigate the effect of 2100 MHz radiofrequency electromagnetic radiation on rat liver tissue and serum paraoxonase 1 level. Materials and Methods: Within the scope of the study, a 2100 MHz radiofrequency electromagnetic radiation model was created. In our study, we used Sprague Dawley male rats. Two groups were made as sham-control and exposure group (5 h a day for 2 weeks). Liver tissue and serum paraoxonase were studied. Results: The paraoxonase 1 value of the exposure group was higher than the sham control group, and did not have statistically important difference in the comparison of exposure and sham control groups (p>0.05). Did not have important difference in histopathological parameters of rat liver tissue (p>0.05). Conclusion: Although it seems that radiofrequency radiation does not cause liver damage, more detailed studies with short- and long-term exposure are needed.